University Instructors’ Enactment of Professional Agency in Teaching Spoken English as a Foreign Language - Wang, Lan; Lam, Ricky (Frontiers in Education, 2022)
Although previous studies on teacher agency have examined its manifestations and significance from the socio-cultural perspective, university English as a foreign language (EFL)-speaking instructors’ professional agency has been underrepresented in the Chinese context. Based on a narrative inquiry approach and cross-case analysis, this qualitative multiple case study explores how four university EFL-speaking instructors exercise their professional agency and the key factors facilitating their agency enactment. The study finds that EFL-speaking instructors work as agentic practitioners to translate their career pursuits into concrete teaching duties, teacher learning, and researching. Their different professional agency enactment is closely related to their agency competence, agency disposition, and identity commitment as well as multifarious contextual factors. The findings imply that understanding the trajectories of teachers’ career development and fostering their teacher agency can assist more practitioners in getting ready for future challenges. It is suggested that frontline teachers hold onto the notion of life-long learning, build academic research profiles, and conduct active reflections to enhance their agency. University administrators should consider creating a more conducive environment to boost EFL-speaking instructors’ agency to facilitate their professional development.